The Effect of Edutech on Purchase Decisions in the Pandemic Era - Nizar Alam hamdani (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2021)
The Covid-19 pandemic has changed people's behavior patterns in getting access to education, Edutech is an alternative in getting technology-based education, The purpose of this study is to examine the influence of Edutech as a public purchase decision maker supported by the power of E-Wom. Study. The research method used in this study is a quantitative method, with a total sample of 250 selected using a simple random sampling technique. Data processing using SEM-PLS. Based on the results of the study, it was found that Edutech with several sizes all had an effect on purchasing decisions. The implication of this research is that the Edutech visualization provided by various platforms is expected to provide convenience in interacting with consumers